Tourette Syndrome as a Disorder of the Social Decision Making Network - Albin, Roger L. (Frontiers in Psychiatry, 2019)
Tourette syndrome is a common neurodevelopmental disorder defined by the presence of tics, stereotyped involuntary movements and phonations. Considerable evidence points to developmental abnormalities of the basal ganglia as tic substrates. Basal ganglia dysfunction does not account for important features of Tourette syndrome, including its natural history, male predominance, and the characteristic quality and distribution of tics. The latter mainly involve eye, face, and head movements, in addition to a variety of simple to complex phonations. A major normal function of these movements, and of phonations well, is social signaling. Many important species- and sex-specific stereotyped social behaviors are mediated by a phylogenetically conserved network of subcortical nuclei, the Social Behavior Network (SBN). Some SBN nuclei are sexually dimorphic and SBN function is modulated strongly by gonadal steroids. Recent studies indicate that the SBN meshes with the basal ganglia to form a larger network, the Social Decision Making Network (SDM; O’Connell and Hofmann [2011]). The SDM concept overlaps significantly with Holstege’s (1993) model of an emotional motor system mediating socially relevant facial movements and phonations. Dopaminergic signaling within the basal ganglia component of the SDM may regulate social act motivation with the SBN component responsible for act expression. Developmental SDM abnormalities can explain all major Tourette syndrome features, including natural history, male predominance, the characteristic distribution of tics, and their stereotyped quality. Some data directly supports this hypothesis. Tourette syndrome may be a disorder of social communication manifesting primarily as abnormal involuntary movements.